The Implementation of International Organization Programs: FAO's Efforts to Address the Food Crisis in Somalia 2021-2024 - Tuswoyo, Sevi Alfrida Abdi; Rasyidah, Resa (Hasanuddin Journal of Strategic and International Studies (HJSIS), 2025)
Food issues have become a sensitive topic because they are one of human life's basic needs and necessities. Somalia is one of the countries suffering from a sustained food crisis over the past few decades. This is caused by factors that have implications for the sustainability of the lives of its people. Therefore, the Food and Agriculture Organization (FAO), an international organization operating in the field of food, has developed strategies through its programs to address the food crisis in Somalia in its efforts to combat famine disasters and achieve sustainable food security. This research uses the theory of International Organization Policy Implementation through the Management Approach as an analytical framework. The methodology used is descriptive with qualitative data analysis techniques. Data was collected through secondary data, namely documents and official publications from related sources. The research findings state that the Food and Agriculture Organization (FAO) implements its programs through monitoring, capacity building, and problem-solving. Monitoring is implemented through an annual reporting system on food crisis conditions, evaluations, and representative visits. Capacity building is achieved by developing individual, organizational, or community capacity through mentoring, skills, knowledge, and training. Problem solving through financial assistance and support. This research aims to provide an overview of the efforts of international organizations to address issues in a country.